미래 산업을 위한 융복합형 디자인 교육에 관한 연구 : PBL(Problem-Based Learning) 수업사례를 중심으로 - 이운형; Lee Woon-hyung (한국디자인포럼, 2020)
연구배경 IT기술을 기반으로 하는 디지털 시대가 도래하면서 디자인 분야는 제품의 대량생산과 소비를 위한 과거의 기능적이고 심미적인 구현 부분에 초점이 맞춰져 있던 것에서 벗어나 소비자와 사용자의 문제 해결과 경험 제공의 수단으로 진화하게 되었다. 대학에서의 디자인 교육 역시 변화하는 시대에 발맞추어 많은 대학에서 여러 다양한 교수법을 활용한 과목의 신설과 편제 변경 등의 자구적인 노력을 통해 시대의 요구에 부응하기 위해 힘써왔으며 이 중 PBL은 창의적인 문제해결능력을 갖추게 하여 협력활동을 통해 지식 배양과 실무적 능력, 의사소통 등의 감각을 익히게 하는 교육 기법으로 많은 각광을 받고 있는 학습 유형이다. 연구방법 본 연구에서는 각 전공 별로 4인의 교육자들이 연구결과 및 교육내용을 공유하고 학생들에게 디자인적인 관점을 중심으로 하여 미래 산업의 핵심분야에서 소비자 및 시장의 특성을 조사 분석할 수 있는 역량을 배양하는 동시에 제품 개발 및 코딩, 제작까지 이루어지는 일련의 과정을 학습하고 이해할 수 있는 PBL방식을 기반으로 한 통합적인 교육 과정 개설과 실행에 대한 연구를 진행하였다. 연구결과 본 연구에서 개발된 융복합형 PBL수업에 참여한 학생들은 소비자 요구 사항 반영을 중심으로 한 스마트폰의 앱 디자인과 개발 과정에서 서로 협력하여 각 팀별로 프로젝트를 진행하였다. 이 과정에서 타 전공 학생들간에 서로 다른 문제 해결 방법을 공유하게 되었고 프로젝트 진행의 각 단계별로 요구되는 역량에 대해 이해하게 되었다. 결론 본 연구에서 제안한 융복합형 PBL수업에서 요구한 스마트폰 앱 개발 프로젝트의 수행을 통해 학생들은 문제해결 과정에서 여러 전공의 협업과 디자인의 역할에 대한 이해도를 높이는 학습 경험을 얻을 수 있었다. 이러한 결과를 통해 PBL수업 사례는 융복합적 디자인 교육에서 앞으로 유용한 수업모형으로서의 발전 가능성을 기대할 수 있을 것이다. Background With the advent of the digital era based on IT technology, the design field has evolved from being focused on functional and aesthetic realization of the past for mass production and consumption of products to a means of solving problems and providing experiences for consumers and users. Design education at universities has also been striving to meet the demands of the times through voluntary efforts such as the establishment of subjects using various teaching methods and changes in organization in many universities to keep pace with the changing times. Among them, PBL is creative problem solving. It is a type of learning that is receiving much attention as an educational technique that allows students to acquire skills and learn a sense of knowledge, practical skills, and communication through cooperation activities. Methods In this paper, four educators for each major share research results and educational content, and focus on design perspectives to students, while cultivating the ability to research and analyze the characteristics of consumers and markets in key areas of the future industry, A study on the establishment and execution of an integrated curriculum based on the PBL method that allows students to learn and understand a series of processes from development, coding and production to production was conducted. Result Students who participated in the convergence PBL class developed in this study cooperated with each other in the process of app design and development of smartphones, focusing on consumer requirements, and carried out projects for each team. In this process, students from other majors shared different problem-solving methods and gained an understanding of the competencies required for each stage of the project. Conclusion Through the implementation of the smartphone app development project required in the convergence PBL class proposed in this study, students were able to gain a learning experience that enhances the understanding of the role of design and collaboration of various majors in the problem solving process. Through these results, the case of PBL class can be expected to develop as a useful teaching model in the future in convergence design education.